Strengthening National Vital Object Security Control to Support National Economic Stability in Indonesia - Prihantoro, Suwandi (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2024)
This research aims to explore the mechanisms that influence critical infrastructure interdependency risk management efforts in Indonesia, with a focus on the transportation, energy and telecommunications sectors. The research used a qualitative approach involving two main sub-studies: document study and in-depth interviews. The main objectives of this research were to understand the dynamics of interdependence between sectors, the importance of collaboration in risk management, and the role of information sharing and responsibility in creating an effective vital object security control system. Data were collected through in-depth interviews and literature studies, with testing of credibility, transferability, triangulation, dependability, and confirmability to ensure the reliability of the results. The results of this study show that the importance of National Vital Objects (Obvitnas) such as PT Bukit Asam Tbk in supporting Indonesia's energy security and economy, as well as challenges in security management that require coordination between relevant agencies and effective technology integration and intersectoral collaboration, information sharing, and strengthening security control systems are key to maintaining national economic stability and operational sustainability of critical infrastructure.Keywords: Risk Management, Critical Infrastructure, Interdependencies, Collaboration, National Vital Objects, Security Controls, Security Technology